DISKRIPSI DAN MANFAAT TANAMAN OBAT DI PEDESAAN SEBAGAI UPAYA PEMBERDAYAAN APOTIK HIDUP (STUDI KASUS DI KECAMATAN WONOKERTO) - Pudjiati Syarif; Bambang Suryotomo(; Hayati Soeprapto (LPPM Universitas Pekalongan, 2011)
This research aims to identify and know the benefits of herbs at the village as a source of traditional medicine and find the villages which have high potential to reserve herbal garden. The methodology of the research is a survey with proporsiv random sampling at Wonokerto, Pekalongan district. The sample of the research is 30 % of 11 villages as the population. They are Wonokerto Kulon, Api-Api, Pesanggrahan, and Sijambe. The result of the research indicates that at the location of the research, there are 40 species of herbs which can be used as a source of traditional medicine. This herbal can be used to cure the diseases, such as: itchy, inflamed, tuberculosis, flu, kidney, diabetic, liver, maag, rheumatic, reducing fat, high tension, heart disease, cancer, and etc. But the utilization of herbs as traditional medicine has not been used by the villagers. The herbs are mostly found in Sijambe village, it means that this village has good potential to develop herbal garden.Key words: Herbal Garden, herbs.